Challenges and opportunities for educating health professionals after the COVID-19 pandemic. Issue 10362 (29th October 2022) - Frenk, Julio; Chen, Lincoln C; Chandran, Latha; Groff, Elizabeth O H; King, Roderick; Meleis, Afaf; Fineberg, Harvey V
Summary: The education of health professionals substantially changed before, during, and after the COVID-19 pandemic. A 2010 Lancet Commission examined the 100-year history of health-professional education, beginning with the 1910 Flexner report. Since the publication of the Lancet Commission, several transformative developments have happened, including in competency-based education, interprofessional education, and the large-scale application of information technology to education. Although the COVID-19 pandemic did not initiate these developments, it increased their implementation, and they are likely to have a long-term effect on health-professional education. They converge with other societal changes, such as globalisation of health care and increasing concerns of health disparities across the world, that were exacerbated by the pandemic. In this Health Policy, we list institutional and instructional reforms to assess what has happened to health-professional education since the publication of the Lancet Commission and how the COVID-19 pandemic altered the education process.